UPAYA PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN KESEHATAN JIWA MELALUI “SEFT” DI WILAYAH KAHURIPAN TASIKMALAYA - Ridwan Kustiawan; Betty Suprapti; Tetet Kartilah; Yanti Cahyati; Yudi Triguna (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Based on the results of the preliminary study that the number of patients with mental disorders registered at the Puskesmas was 22 person while data on risk disorders and mental health communities did not yet exist. Therefore it is necessary to form mental health Kader to identify and maintain the mental health of the community through Kader. This community service activity consists of three activities, namely mental health Kader training activities, early detection of mental health problems and, mental health counseling activities. Kader training activities were carried out using lecture, question and answer methods, and role play. Activities for early detection of mental health problems are carried out by Kader as well. Outreach activities to the community about mental health are carried out together with Kader. The participation of Kader who attended were targeted at 80%, in fact 98% attended. There was an increase in knowledge from the pre and post scores, namely the pre-test score of 72 to 85 post-test scores. The discovery of new cases of clients with mental disorders that had not previously been recorded in the public health's data.